Ø·Ø±Ù‚ Ù…Ù‚ØªØ±ØØ© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ ÙÙŠ Ø¨Ø¯Ø§ÙŠØ© ØªØ¹Ù„Ù…Ù‡Ù… - Abdurrohman, Wahid (El-Hayah, 2021)
Â AbstractKnowing the suitable methods to break the wall of Arab vocal difficulties faced by learners at the beginning of their learning Arabic language is one of the most important weapons that teachers must arm themselves to achieve their goal. Arabic has a sound system that is different from other languages in the world, as the imbalance in the teaching of sounds affects the acquisition of the correct target vocabulary. The researcher took the qualitative method of descriptive analytical in the completion of this study, through which the researcher collected data from books and documents related to the teaching and analysis of votes. This study has shown by presenting suitable proposal methods for teaching Arabic voices to beginner students, one of them is using the three methods of sound exercises that are sound identification, sound distinguishing, and abstract sound identification (identifying sound from sentences), and also by language games, by adjusting our self in speaking and listening to Arabic language that is correct, by tahsin Al Quran by professional supervisor, and by good Arabic songs.Keywords: Teaching methods, Arabic language, Arabic vocal. Â Â Ù…Ù„Ø®Øµ Ø§Ù„Ø¨ØØ«Ø¥Ù† Ù…Ø¹Ø±ÙØ© Ø§Ù„Ø·Ø±Ù‚ Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø© Ù„ÙƒØ³Ø± Ø¬Ø¯Ø§Ø± Ø§Ù„ØµØ¹ÙˆØ¨Ø§Øª Ø§Ù„ØµÙˆØªÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„ØªÙŠ ÙŠÙˆØ§Ø¬Ù‡Ù‡Ø§ Ø§Ù„Ø¯Ø§Ø±Ø³ÙˆÙ† ÙÙŠ Ø¨Ø¯Ø§ÙŠØ© ØªØ¹Ù„Ù…Ù‡Ù… Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ø£Ù‡Ù… Ø§Ù„Ø£Ø³Ù„ØØ© Ø§Ù„ØªÙŠ Ù„Ø§ Ø¨Ø¯ Ù…Ù† Ø§Ù„Ù…Ø¯Ø±Ø³ÙŠÙ† Ø£Ù† ÙŠØªØ³Ù„ØÙˆØ§ Ø¨Ù‡Ø§ Ù„ØªØÙ‚ÙŠÙ‚ Ù‡Ø¯ÙÙ‡Ù… ÙƒØ³Ø± Ù‡Ø°Ø§ Ø§Ù„Ø¬Ø¯Ø§Ø±. ÙØ¥Ù† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù‡Ø§ Ù†Ø¸Ø§Ù… ØµÙˆØªÙŠ ÙŠØ®ØªØµ Ø¨Ù‡Ø§ Ø¹Ù† Ø³Ø§Ø¦Ø± Ø§Ù„Ù„ØºØ§Øª ÙÙŠ Ø§Ù„Ø¹Ø§Ù„Ù…ØŒ ÙØ§Ù„Ø®Ù„Ù„ ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ø£ØµÙˆØ§Øª ÙŠØ¤Ø«Ø± ÙÙŠ Ø§ÙƒØªØ³Ø§Ø¨ Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ù‡Ø¯Ù Ø§Ù„ØµØÙŠØØ©. ÙˆØ³Ù„Ùƒ Ø§Ù„Ø¨Ø§ØØ« Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù†ÙˆØ¹ÙŠ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠ ÙÙŠ Ø¥Ù†Ø¬Ø§Ø² Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø©ØŒ ÙˆØ§Ù„Ø°ÙŠ Ù…Ù† Ø®Ù„Ø§Ù„Ù‡ Ù‚Ø§Ù… Ø§Ù„Ø¨Ø§ØØ« Ø¨Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø§Ù„ÙƒØªØ¨ ÙˆØ§Ù„ÙˆØ«Ø§Ø¦Ù‚ Ø§Ù„Ù…ØªØ¹Ù„Ù‚Ø© Ø¨ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ø£ØµÙˆØ§Øª ÙˆÙ…Ù† Ø«Ù… ØªØÙ„ÙŠÙ„Ù‡Ø§. ÙˆÙ‚Ø¯ Ø£Ø«Ø¨ØªØª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¨Ø¹Ø±Ø¶ Ø·Ø±Ù‚ Ù…Ù‚ØªØ±ØØ© Ù…Ù†Ø§Ø³Ø¨Ø© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¨ØªØ¯Ø¦ÙŠÙ†ØŒ Ù…Ù†Ù‡Ø§Ø› Ø§Ù„ØªØ¯Ø±ÙŠØ¨Ø§Øª Ø§Ù„ØµÙˆØªÙŠØ© Ø§Ù„Ø«Ù„Ø§Ø«Ø© ÙˆÙ‡ÙŠ Ø§Ù„ØªØ¹Ø±Ù Ø§Ù„ØµÙˆØªÙŠ ÙˆØ§Ù„ØªÙ…ÙŠÙŠØ² Ø§Ù„ØµÙˆØªÙŠ ÙˆØ§Ù„ØªØ¬Ø±ÙŠØ¯ Ø§Ù„ØµÙˆØªÙŠØŒ ÙˆØ§Ù„Ø£Ù„Ø¹Ø§Ø¨ Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆÙ…Ù…Ø§Ø±Ø³Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ Ø¥Ù„Ù‰ Ø£ØµÙˆØ§ØªÙ‡Ø§ Ø§Ù„ØµØÙŠØØ©ØŒ ÙˆØªØØ³ÙŠÙ† Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ø¹Ù„Ù‰ Ø£ÙŠØ¯ÙŠ Ø§Ù„Ù…Ø´Ø§ÙŠØ® Ø§Ù„Ù…Ø¬ÙŠØ¯ÙŠÙ†ØŒ ÙˆÙ…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ø£Ù†Ø§Ø´ÙŠØ¯ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©.Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙØªØ§ØÙŠØ©: Ø·Ø±Ù‚ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ØŒ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©